Alexithymia, Not Autism Spectrum Disorder, Predicts Perceived Attachment to Parents in School-Age Children - Giannotti, Michele; de Falco, Simona; Venuti, Paola (Frontiers in Psychology, 2020)
Alexithymia is defined as a limited ability in the cognitive processing of emotions. Literature suggested its negative influence on interpersonal relationship, documenting elevated alexithymia in individuals with Autism Spectrum Disorder (ASD) compared to control groups. However, the study of alexithymia in school-age children with ASD remains largely unexplored as well as its effect on specific child socioemotional outcomes such as quality of attachment relationships. This study examines alexithymia and perceived attachment to parents in twenty-four children with ASD (without intellectual disability) and 24 typically developing (TD) children (mean age 10 years) using the self-reported Alexithymia Questionnaire for Children (AQC) and the Inventory of Parent and Peer Attachment (IPPA). Measures of family SES as well as child intelligence were collected. Data revealed that ASD children showed higher levels of Alexithymia compared to TD group. In addition, 21% of participants with ASD exceed alexithymia categorical cut-off. By contrast, no difference emerged in the perception of attachment to parents. Moreover, alexithymia, but not ASD status, was found to predictive of child perception of attachment to parents. We observed no significant effect of child age and verbal IQ. Our findings showed that alexithymia was more common in children with ASD, whereas attachment was similar between groups. Difficulties in identifying and describing one’s own feelings may hinder the construction of a positive representation of parent-child attachment relationship regardless of child clinical status. Thus, alexithymia seems to play a key role on the way school-age children with and without ASD perceive their relationship with their parents.